A New Two-Step Methodology for CANDU Analysis with the APEC-Assisted Nodal Equivalence Theory. (2nd September 2019) - Motalab, Mohammad Abdul; Kim, Woosong; Kim, Yonghee
Abstract: This paper is concerned with an improved two-step methodology based on the nodal equivalence theory for more accurate and consistent CANDU reactor analysis. In addition, the albedo-corrected parameterized equivalence constants (APEC) method is introduced to achieve further improvement of the nodal solution by correcting the burnup-dependent cross sections (XSs) and discontinuity factors (DFs). The APEC algorithm is incorporated into an in-house nodal expansion method (NEM) code. Colorset calculations are performed to obtain physically meaningful leakage information of the fuel lattice, and the results are used for generating burnup-dependent APEC functions to correct groupwise XSs and DFs. The NEM-equivalent reference DF on each surface of the colorset are calculated for a coarse mesh (1 × 1 mesh per fuel assembly) using the net-current boundary conditions. These reference DFs are used to determine the DF APEC functions. A separate set of burnup-dependent APEC functions is generated for the fuel lattice loaded with a reactivity device. Both position- and burnup-dependent APEC functions are applied for accurate CANDU core analysis. A two-dimensional CANDU whole-core nodal analysis is performed to show the effectiveness of the APEC corrections. Moreover, several variants of the original benchmark are also analyzed with the same APEC functions to confirm the general applicability of the predetermined APEC functions. In addition, NEM calculations are performed for a CANDU core with a reactivity device and its variants with different burnup profiles. Numerical results show that the APEC-based two-step nodal methodology can provide an accurate and consistent solution for burned CANDU cores with reactivity device.